Fabrication and characterization of p-n junctions based on ZnO and CuPc - Gupta, R. K.; Yakuphanoğlu, Fahrettin; Ghosh, K.; Kahol, P. K. (Elsevier Science Bv, 2011)
p-n Junctions based on zinc oxide (ZnO) and copper-phthalocyanine (CuPc) were fabricated using pulsed laser deposition and thermal evaporator techniques, respectively. Current-voltage (I-V) characteristics of the ZnO-CuPc junction showed rectifying behavior. Various junction parameters such as barrier height and ideality factor were calculated using I-V data and observed to be 0.63 +/- 0.02 eV and 4.0 +/- 0.3, respectively. Cheung and Norde's method were used to compare the junction parameters obtained by I-V characteristics. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: p-n Junction; ZnO; CuPc; Pulsed laser; Thermal evaporator; Thin films; Semiconductor